Shape transfer film

By designing a shape transfer film with a specific concave and convex shape, the problem of difficult peeling of the shape transfer film in the prior art is solved, while ensuring sufficient covering of the protective layer, achieving the dual effects of covering and peeling ease.

CN114902819BActive Publication Date: 2025-03-04TATSUTA ELECTRICWIRE & CABLE
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202180007796.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2020-01-09
Filing Date
2021-01-08
Publication Date
2025-03-04
Estimated Expiration
2041-01-08

AI Technical Summary

Technical Problem

When the conventional shape transfer film is laminated with the protective layer, the anchoring effect of the concave and convex shape makes it difficult to peel off from the protective layer, or the protective layer will be taken away when peeled off, affecting the covering property.

Method used

A shape transfer film with a specific concave and convex shape on the surface is designed, with an interface expansion area ratio of Sdr of 1500 to 7000%, and a horizontal difference Sk of the central part is 2.0 to 7.0 μm, which is used to transfer shapes derived from these concave and convex shapes to the transfer object to ensure covering and peeling.

Benefits of technology

It is realized that sufficient covering is given to the transfer object, and at the same time, the shape transfer film can be easily peeled off when intentionally peeled off to avoid taking away the protective layer.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN114902819B_ABST
    Figure CN114902819B_ABST
Patent Text Reader

Abstract

The present invention provides a shape transfer film, which is a shape transfer film containing a concave-convex shape, which can give a transfer object sufficient hiding power by transferring a shape derived from the concave-convex shape to the transfer object, and can be easily peeled off from the transfer object when it is intended to be peeled off. The shape transfer film 1 contains a concave-convex shape with an interface development area ratio Sdr of 1500 to 7000% and / or a level difference Sk of 2.0 to 7.0 μm in the center on at least one side, and is used to transfer a shape derived from the concave-convex shape to the transfer object. The shape transfer film 1, for example, includes a substrate layer 2 and a resin layer 3 provided on one side of the substrate layer 2. And the shape transfer film 1, for example, contains a filler 4, and the concave-convex shape is formed by the filler 4 protruding outward more than the flat surface 3a of the film.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a shape transfer film. More specifically, the present invention relates to a shape transfer film for transferring a shape derived from a concavo-convex shape contained in the shape transfer film to a transfer object. Background Art

[0002] Printed circuit boards are widely used to assemble circuits into mechanisms in electronic devices such as mobile phones, cameras, and notebook personal computers. They are also used to connect movable parts such as print heads and control parts. In these electronic devices, electromagnetic wave shielding measures must be taken, and even printed circuit boards used in devices use shielded printed circuit boards that implement electromagnetic wave shielding measures.

[0003] Electromagnetic wave shielding films are used to shield printed wiring boards. For example, electromagnetic wave shielding films used in conjunction with printed wiring boards include a conductive adhesive layer, a protective layer for protecting the conductive adhesive layer and a shielding layer such as a metal layer provided as needed.

[0004] In recent years, in a shielded printed circuit board, the protective layer that becomes the outermost layer of the electromagnetic wave shielding film stacked on the printed circuit board is sometimes required to present an appearance with low surface gloss for the purpose of hiding the circuit pattern. The protective layer with low surface gloss can be listed as a protective layer having a concave-convex shape on the surface. Such a protective layer can be made, for example, as follows: a composition for forming a protective layer is cast on the concave-convex surface of a transfer film (shape transfer film) having a concave-convex shape on the surface, and then cured to form a protective layer, thereby giving (transferring) a shape of the concave-convex shape derived from the shape transfer film to the surface of the protective layer, and performing a matte process.

[0005] For example, Patent Document 1 discloses the above-mentioned shape transfer film.

[0006] Prior art literature

[0007] Patent Literature

[0008] Patent document 1: Japanese Patent Application Laid-Open No. 2017-71107. Summary of the invention

[0009] Technical problem to be solved by the invention

[0010] However, in the conventional shape transfer film provided with a concavo-convex shape for the purpose of imparting hiding property to the protective layer, the anchoring effect derived from the concavo-convex shape works when it is laminated with the protective layer, so that it is difficult to peel off the shape transfer film from the protective layer, or even if the shape transfer film is peeled off, the protective layer is peeled off together. If the concavo-convex shape is made shallow, the anchoring effect can be weakened, and the shape transfer film can be easily peeled off from the state of being adhered to the protective layer, but the concavo-convex shape formed on the protective layer will also become shallow, so that sufficient hiding property cannot be imparted to the protective layer.

[0011] The present invention has been made in view of the above-mentioned problems, and its object is to provide a shape transfer film, which is a shape transfer film containing a concave-convex shape, and can give the transfer object sufficient covering properties by transferring a shape derived from the above-mentioned concave-convex shape to the transfer object, and can be easily peeled off from the transfer object when it is intended to be peeled off.

[0012] Technical means to solve technical problems

[0013] The inventors of the present application have made careful research to achieve the above-mentioned purpose and found that a shape transfer film having a specific concavo-convex shape on its surface can impart sufficient covering properties to a transfer object by transferring a shape derived from the concavo-convex shape to the transfer object, and can be easily peeled off from the transfer object when it is intended to be peeled off. The present invention is completed based on the above-mentioned discovery.

[0014] The present invention provides a shape transfer film, wherein at least one surface of the shape transfer film has a concavo-convex shape with an interface development area ratio Sdr of 1500 to 7000%, and is used for transferring a shape derived from the concavo-convex shape to a transfer object.

[0015] Preferably, the level difference Sk at the center of the concavo-convex shape is 2.0 to 7.0 μm.

[0016] The present invention also provides a shape transfer film having at least one surface thereof having a concavo-convex shape with a center level difference Sk of 2.0 to 7.0 μm, and used for transferring a shape derived from the concavo-convex shape to a transfer object.

[0017] Preferably, the arithmetic mean height Sa of the concavo-convex shape is 1.0 to 2.0 μm.

[0018] Preferably, the root mean square height Sq of the concavo-convex shape is 1.0 to 2.8 μm.

[0019] Preferably, the root mean square slope Sdq of the concavo-convex shape is 7-15.

[0020] Preferably, a ratio of an interface development area ratio Sdr to a root mean square slope Sdq [Sdr / Sdq] in the concavo-convex shape is 200-500.

[0021] Preferably, the shape transfer film includes a substrate layer and a resin layer provided on one surface of the substrate layer, and the surface of the resin layer has the concavo-convex shape.

[0022] Preferably, the shape transfer film contains a filler, and the concavo-convex shape is formed by the filler protruding outward from a flat surface of the film.

[0023] Furthermore, the present invention provides an attachment film for a printed wiring board, the attachment film for a printed wiring board comprising the shape transfer film and a circuit pattern covering layer directly laminated with the shape transfer film.

[0024] Preferably, in the attached film for a printed wiring board, an adhesive layer, the circuit pattern concealing layer, and the shape transfer film are laminated in this order.

[0025] Preferably, the 85° glossiness of the surface of the circuit pattern covering layer on the shape transfer film side is 15 or less.

[0026] Effects of the Invention

[0027] According to the shape transfer film of the present invention, since the surface thereof contains the above-mentioned specific concavo-convex shape, sufficient covering property can be given to the transfer object by giving the transfer object a shape derived from the above-mentioned concavo-convex shape, and the shape transfer film can be easily peeled off from the transfer object when it is intentionally peeled off from the transfer object. In addition, the shape transfer film is difficult to be peeled off from the transfer object except when it is intentionally peeled off during transportation. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] [ Figure 1 ] A schematic cross-sectional view of an embodiment of a shape transfer film of the present invention;

[0029] [ Figure 2 ] A schematic cross-sectional view of another embodiment of the shape transfer film of the present invention;

[0030] [ Figure 3 ]use Figure 1 A schematic cross-sectional view of one embodiment of an adhesive film for a printed wiring board having a shape transfer film shown. DETAILED DESCRIPTION

[0031] [Shape transfer film]

[0032] The shape transfer film according to one embodiment of the present invention has a concavo-convex shape on at least one side, and is used to impart (transfer) a shape derived from the concavo-convex shape to a transfer object. The shape transfer film is particularly preferably used to impart (transfer) a shape derived from the concavo-convex shape to the outermost layer (e.g., a circuit pattern masking layer described later) of a film (printed wiring board attachment film) for attachment to a printed wiring board.

[0033] In the above-mentioned concavo-convex shape contained in the above-mentioned shape transfer film, the interface development area ratio Sdr is preferably 1500-7000%, more preferably 2000-6500%, and further preferably 2500-6000%. The above-mentioned interface development area ratio Sdr is based on ISO25178 and is an indicator of how much the development area (surface area) of the defined area increases relative to the area of ​​the above-mentioned defined area. The Sdr of a completely flat surface is 0%. If the above-mentioned interface development area ratio Sdr is 1500% or more, it is possible to give sufficient covering properties to the transfer object to which the shape derived from the above-mentioned concavo-convex shape is given. If the above-mentioned interface development area ratio Sdr is 7000% or less, it will be easy to intentionally peel off the shape transfer film from the transfer object.

[0034] In the above-mentioned concavo-convex shape, the level difference Sk of the center portion is preferably 2.0 to 7.0 μm, more preferably 2.3 to 6.0 μm, and further preferably 2.5 to 5.0 μm. The level difference Sk of the above-mentioned center portion is based on ISO25178, and is the value obtained by subtracting the minimum height of the center portion in the concavo-convex shape. The center portion is an area sandwiched by the heights of 0% and 100% of the load area rate of the equivalent straight line. If the level difference Sk of the above-mentioned center portion is greater than 2.0 μm, the height difference of the center portion is large, and sufficient covering power can be given to the transfer object to which the shape derived from the above-mentioned concavo-convex shape is given. If the level difference Sk of the above-mentioned center portion is less than 7.0 μm, it will become easy to intentionally peel off the shape transfer film from the transfer object.

[0035] In the above-mentioned concavo-convex shape, the arithmetic mean height Sa is preferably 1.0 to 2.0 μm, more preferably 1.0 to 1.8 μm, and further preferably 1.0 to 1.6 μm. The above-mentioned arithmetic mean height Sa is based on ISO25178, and represents the average value of the absolute value of the difference in height of each point relative to the average plane of the surface. If the above-mentioned arithmetic mean height Sa is greater than 1.0 μm, it is possible to impart more sufficient covering properties to the transfer object to which the shape derived from the above-mentioned concavo-convex shape is given. If the above-mentioned arithmetic mean height Sa is less than 2.0 μm, it will become easier to intentionally peel off the shape transfer film from the transfer object.

[0036] In the above-mentioned concavo-convex shape, the root mean square height Sq is preferably 1.0 to 2.8 μm, more preferably 1.1 to 2.5 μm, and further preferably 1.3 to 2.0 μm. The above-mentioned root mean square height Sq is based on ISO25178 and is a parameter equivalent to the standard deviation of the distance from the average surface. If the above-mentioned root mean square height Sq is greater than 1.0 μm, it is possible to impart more sufficient covering properties to the transfer object to which the shape derived from the above-mentioned concavo-convex shape is given. If the above-mentioned root mean square height Sq is less than 2.8 μm, there is less unevenness in the height of the concavo-convex shape, and it will be easier to intentionally peel off the shape transfer film from the transfer object.

[0037] In the above-mentioned concave-convex shape, the root mean square inclination Sdq is preferably 7 to 15, more preferably 8 to 14, and further preferably 9 to 13.5. The above-mentioned root mean square inclination Sdq is based on ISO25178, and is a parameter calculated based on the root mean square of the inclination at all points in the defined area. The Sdq of a completely flat surface is 0. If the above-mentioned root mean square inclination Sdq is 7 or more, it is possible to impart more sufficient covering power to the transfer object to which the shape derived from the above-mentioned concave-convex shape is given. If the above-mentioned root mean square inclination Sdq is 15 or less, there is less unevenness in the height of the concave-convex shape, and it will become easier to intentionally peel off the shape transfer film from the transfer object.

[0038] In the above-mentioned concavoconvex shape, the ratio of the interface development area ratio Sdr [%] to the root mean square inclination Sdq [Sdr / Sdq] is preferably 200 to 500, more preferably 250 to 480, and further preferably 300 to 450. If the above ratio is 200 or more, the surface area becomes larger (i.e., the concavoconvex undulation is drastic), and it is presumed that a more sufficient covering property can be given to the transfer object to which the shape derived from the above-mentioned concavoconvex shape is given. If the above ratio is 500 or less, the inclination of the concavoconvex can be suppressed and the surface area (i.e., the degree of concavoconvex undulation) can also be suppressed within a certain range, thereby making it easier to intentionally peel the shape transfer film from the transfer object.

[0039] The 60° glossiness of the above-mentioned concave-convex shape is preferably 4.0 or more, more preferably 4.5 or more, and further preferably 5.0 or more. If the above-mentioned 60° glossiness is 4.0 or more, it is presumed that the above-mentioned concave-convex shape will become a shape more suitable for intentional peeling, and it will become easier to intentionally peel off the shape transfer film from the transfer object. The 60° glossiness of the above-mentioned concave-convex shape is preferably 20 or less, more preferably 15 or less, and further preferably 10 or less. If the above-mentioned 60° glossiness is 20 or less, it is presumed that the above-mentioned concave-convex shape will become a shape more suitable for intentional peeling, and can give the transfer object more sufficient hiding power. The above-mentioned 60° glossiness can be measured by a method based on JIS Z8741.

[0040] The 85° glossiness of the concavo-convex shape is preferably 2.5 to 15.0, more preferably 3.0 to 13.0. When the 85° glossiness is 2.5 or more, it becomes easier to intentionally peel the shape transfer film from the transfer object. When the 85° glossiness is 15.0 or less, it is possible to impart more sufficient hiding power to the transfer object. The 85° glossiness can be measured by a method in accordance with JIS Z 8741.

[0041] One embodiment of the shape transfer film may include, for example, a substrate layer and a resin layer provided on at least one side of the substrate layer, wherein the side surface of the resin layer includes the concave-convex shape. Other embodiments of the shape transfer film may include a shape transfer film having the concave-convex shape on the surface of the substrate layer. The shape transfer film involved in the other embodiments may include a shape transfer film having a concave-convex shape by pressing a mold having a concave-convex shape against the substrate layer.

[0042] In the shape transfer film, the concavo-convex shape can be formed by a well-known or even commonly used method, and the various characteristics mentioned above can be included in the formation. The method of forming the concavo-convex shape can include, for example, a method of roughening the flat surface by physical means such as a method of sandblasting the flat surface, a method of spraying dry ice on the flat surface, a method of pressing a mold containing a concavo-convex shape, a method of mixing a filler so that it protrudes outward from the flat surface of the shape transfer film, etc. The above methods can be used alone or in combination of two or more.

[0043] The embodiment of the shape transfer film in which a filler is blended to form a concavoconvex shape can be exemplified by: Figure 1 and Figure 2 Transfer film to the shape shown. Figure 1 The shape transfer film 1 shown includes a substrate layer 2 and a resin layer 3 provided on one side of the substrate layer 2, and the side surface of the resin layer 3 has the above-mentioned concavo-convex shape. The resin layer 3 contains fillers 4, and the fillers 4 protrude outward from the flat surface 3a of the resin layer 3, which is the flat surface of the film, thereby forming the above-mentioned concavo-convex shape.

[0044] The above-mentioned substrate layer can for example include porous materials such as plastic substrate (especially plastic film), paper, cloth, nonwoven fabrics, net, foam sheet, metal foil, etc. The above-mentioned substrate layer can be a single layer, or a laminate of the same or different substrates. In addition, the surface of the above-mentioned substrate layer can also be suitably subjected to known commonly used surface treatments such as physical treatments such as corona discharge treatment, plasma treatment, chemical treatments such as primer treatment, etc.

[0045] The resin constituting the above-mentioned plastic substrate can be listed, for example, low-density polyethylene, linear low-density polyethylene, medium-density polyethylene, high-density polyethylene, ultra-low-density polyethylene, random copolymer polypropylene, block copolymer polypropylene, homopolymer polypropylene, polybutene, polymethylpentene, ethylene-vinyl acetate copolymer (EVA), ionomer, ethylene-(meth)acrylic acid copolymer, ethylene-(meth)acrylate (random, alternating) copolymer, ethylene-butene copolymer, ethylene-hexene copolymer and other polyolefin resins; polyurethane; polyesters such as polyethylene terephthalate (PET), polyethylene naphthalate, polybutylene terephthalate (PBT); polycarbonate; polyimide; polyetheretherketone; polyetherimide; polyamides such as aramid and wholly aromatic polyamide; polyphenylene sulfide; fluorocarbon resin; polyvinyl chloride; polyvinylidene chloride; cellulose resin; silicone resin, etc. The above-mentioned resins can be used alone or in combination.

[0046] The resin forming the above-mentioned resin layer is not particularly limited, and examples thereof include thermoplastic resins, thermosetting resins, active energy ray-curable resins and other curable resins. In this specification, "curable resin" is a concept that includes both resins that can be cured to form resins (curable resins) and resins formed by curing curable resins. Among them, the above-mentioned resin is preferably a curable resin from the viewpoint of excellent peelability from the circuit pattern cover layer described later after curing, and is particularly preferably an active energy ray-curable resin from the viewpoint that the degree of curing is difficult to change when the printed wiring board attachment film is thermally pressed onto the printed wiring board. The above-mentioned resins can be used alone or in combination of two or more.

[0047] Examples of the thermoplastic resin include polystyrene resins, vinyl acetate resins, polyester resins, polyolefin resins (eg, polyethylene resins, polypropylene resin compositions, etc.), polyimide resins, and acrylic resins.

[0048] Examples of the thermosetting resin include phenolic resins, epoxy resins, polyurethane resins, melamine resins, alkyd resins, and silicone resins.

[0049] Examples of the epoxy resin include bisphenol epoxy resins, spirocycle epoxy resins, naphthalene epoxy resins, biphenyl epoxy resins, terpene epoxy resins, glycidyl ether epoxy resins, glycidyl amine epoxy resins, and novolac epoxy resins.

[0050] Examples of the bisphenol epoxy resins include bisphenol A epoxy resins, bisphenol F epoxy resins, bisphenol S epoxy resins, and tetrabromobisphenol A epoxy resins. Examples of the glycidyl ether epoxy resins include tris(glycidyloxyphenyl)methane and tetra(glycidyloxyphenyl)ethane. Examples of the glycidylamine epoxy resins include tetraglycidyldiaminodiphenylmethane. Examples of the (linear) novolac epoxy resins include cresol (linear) novolac epoxy resins, phenol (linear) novolac epoxy resins, α-naphthol (linear) novolac epoxy resins, and brominated phenol (linear) novolac epoxy resins.

[0051] Examples of the active energy ray-curable resin include polymerizable resins containing at least two free radical reactive groups (e.g., (meth)acryloyl groups) in the molecule. Examples of the active energy ray include electron beams, ultraviolet rays, α rays, β rays, γ rays, and X rays.

[0052] Examples of the filler include organic particles and inorganic particles. Examples of the organic particles include acrylic resins such as polymethyl methacrylate, polyacrylonitrile resins, polyurethane resins, polyamides, polyimides, etc. Examples of the inorganic particles include calcium carbonate, calcium silicate, clay, porcelain clay, talc, silicon dioxide, glass, diatomaceous earth, mica powder, aluminum oxide, magnesium oxide, zinc oxide, barium sulfate, aluminum sulfate, calcium sulfate, magnesium carbonate, etc. Only one type of the particles may be used, or two or more types may be used.

[0053] The median diameter (D50) of the filler is not particularly limited, but is preferably 0.5 to 20 μm, more preferably 1 to 10 μm. If D50 is within the above range, the above concavo-convex shape can be easily formed. The above D50 refers to the particle size at the cumulative value of 50% in the particle size distribution obtained by laser diffraction / scattering method.

[0054] The content of the filler in the resin layer is not particularly limited, but is preferably 20 to 70 parts by mass, more preferably 30 to 60 parts by mass, relative to 100 parts by mass of the resin forming the resin layer. If the content is within the above range, the concavo-convex shape can be easily formed.

[0055] The thickness of the resin layer (the thickness between the two flat surfaces) is not particularly limited, but is preferably 0.5 to 9 μm, and more preferably 1 to 7 μm. If the thickness is within the above range, the shape of the filler protruding from the flat surface can be within an appropriate range due to the relationship with the D50 of the filler, and the above concavo-convex shape can be easily formed.

[0056] The resin layer 3 can be formed on the substrate layer 2 in a manner including the above-mentioned concavo-convex shape by a well-known or even commonly used method to produce Figure 1The shape transfer film 1 shown in the figure can be produced by, for example, casting a composition containing a resin or compound forming the resin layer and a filler and, if necessary, a solvent on one side of a substrate layer, and then removing the solvent or curing it to cure it.

[0057] Figure 2 In the shape transfer film 1 shown, the surface of the substrate layer 2 has the above-mentioned uneven shape. The substrate layer 2 contains fillers 4, and the fillers 4 protrude outward from the flat surface 2a of the substrate layer 2, which is the flat surface of the film, to form the above-mentioned uneven shape.

[0058] A release treatment layer may be provided on the surface of the substrate layer having the concavo-convex shape. The release treatment layer may be a layer formed by surface treatment with a release treatment agent such as silicon, long-chain alkyl, fluorine, molybdenum sulfide, etc. When the release treatment layer is included, the thickness and shape of the release treatment layer are appropriately set so that the concavo-convex shape on the surface of the substrate layer does not disappear, that is, the shape transfer film contains the concavo-convex shape.

[0059] The substrate layer containing the above-mentioned release treatment layer can be listed as the substrate layer exemplified and explained as the substrate layer containing the above-mentioned resin layer. The substrate layer without the above-mentioned release treatment layer can be listed as a low bonding substrate composed of a fluorine-containing polymer, a low bonding substrate composed of a non-polar polymer, etc. The fluorine-based polymers in the above-mentioned low bonding substrate composed of a fluorine-containing polymer can be listed, for example, polytetrafluoroethylene, polytrifluorochloroethylene, polyvinyl fluoride, polyvinylidene fluoride, tetrafluoroethylene-hexafluoropropylene copolymer, chlorofluoroethylene-vinylidene fluoride copolymer, etc. In addition, the above-mentioned non-polar polymer can be listed, for example, olefin resins (such as polyethylene, polypropylene, etc.). The surface of the above-mentioned substrate layer can be appropriately applied with well-known and commonly used surface treatments such as physical treatments such as corona discharge treatment and plasma treatment, and chemical treatments such as primer treatment.

[0060] Examples of the filler include the fillers exemplified and described above as the material contained in the resin layer.

[0061] The median diameter (D50) of the filler is not particularly limited, but is preferably 0.5 to 20 μm, more preferably 1 to 10 μm. If D50 is within the above range, the above concavo-convex shape can be easily formed. The above D50 refers to the particle size at the cumulative value of 50% in the particle size distribution obtained by laser diffraction / scattering method.

[0062] The content of the filler in the substrate layer is not particularly limited, but is preferably 10 to 70% by volume, more preferably 20 to 60% by volume, and further preferably 30 to 50% by volume relative to 100% by volume of the total volume of the substrate layer. If the content is within the above range, the concavo-convex shape can be easily formed.

[0063] The substrate layer 2 can be formed by a well-known or even commonly used method so that at least one surface thereof has the above-mentioned concavo-convex shape to produce Figure 2 The shape transfer film 1 shown in the figure can be produced by kneading the filler in the resin composition forming the substrate layer and molding it. Then, a release agent can be applied and cured as needed to form a release treatment layer.

[0064] The layer containing the above-mentioned concavo-convex shape (resin layer, substrate layer) may contain other components other than the above-mentioned components within the range that does not impair the effect of the present invention. The above-mentioned other components can be listed, for example, as colorants, antistatic agents, stabilizers, antioxidants, ultraviolet absorbers, fluorescent whitening agents, etc. The above-mentioned other components can be used alone or in combination of two or more.

[0065] The thickness of the shape transfer film is not particularly limited, and is, for example, 10 to 200 μm, preferably 15 to 150 μm. When the thickness is 10 μm or more, the protection performance of the transfer object is more excellent. When the thickness is 200 μm or less, it is easier to peel off during use.

[0066] According to the shape transfer film, since the surface thereof includes the specific concavo-convex shape, the transfer object can be given sufficient covering property by giving the transfer object a shape derived from the concavo-convex shape, and the shape transfer film can be easily peeled off from the transfer object when it is intentionally peeled off. In addition, the shape transfer film is difficult to be peeled off from the circuit pattern covering layer except when it is intentionally peeled off during transportation.

[0067] [Attachment film for printed circuit boards]

[0068] The attached film for printed wiring board involved in one embodiment of the present invention comprises the above-mentioned shape transfer film and a circuit pattern covering layer directly laminated with the above-mentioned shape transfer film. The shape derived from the above-mentioned concave-convex shape is imparted (transferred) to the surface of the circuit pattern covering layer directly laminated with the surface of the above-mentioned shape transfer film containing the above-mentioned concave-convex shape. As a result, when the above-mentioned shape transfer film is intentionally peeled off, it can be easily peeled off from the above-mentioned circuit pattern covering layer, and the above-mentioned circuit pattern covering layer after peeling off has sufficient covering property.

[0069] The above-mentioned attachment film for printed wiring board preferably has an adhesive layer, the above-mentioned circuit pattern concealing layer and the above-mentioned shape transfer film laminated in this order. The above-mentioned attachment film for printed wiring board may also include a layer other than the above-mentioned adhesive layer, the above-mentioned circuit pattern concealing layer and the above-mentioned shape transfer film.

[0070] Hereinafter, one embodiment of the above-mentioned attachment film for a printed wiring board will be described. Figure 3 It is a schematic cross-sectional view of one embodiment of the above-mentioned attachment film for a printed wiring board.

[0071] Figure 3The printed circuit board attachment film 5 shown in the figure comprises an adhesive layer 7, a circuit pattern covering layer 6, Figure 1 The shape transfer film 1 is shown. More specifically, the adhesive film 5 for printed circuit boards is directly laminated with a protective layer for protecting the adhesive layer 7, namely, a circuit pattern covering layer 6, on one side of the adhesive layer 7. When the adhesive film 5 for printed circuit boards uses a conductive adhesive layer as the adhesive layer 7, the conductive adhesive layer functions as an electromagnetic wave shielding layer and exerts electromagnetic wave shielding performance. At this time, the adhesive film 5 for printed circuit boards can be used as an electromagnetic wave shielding film. In addition, when the adhesive layer 7 does not have shielding performance or requires higher shielding performance, other electromagnetic wave shielding layers such as a metal layer may be included between the circuit pattern covering layer and the adhesive layer. At this time, the circuit pattern covering layer is indirectly laminated with the adhesive layer.

[0072] The shape transfer film 1 is laminated on the surface of the circuit pattern covering layer 6 opposite to the adhesive layer 7, and the circuit pattern covering layer 6 is in contact with the resin layer 3. The surface of the circuit pattern covering layer 6 is directly laminated on the surface of the shape transfer film 1 having the above-mentioned concavo-convex shape, so that a shape derived from the above-mentioned concavo-convex shape is imparted (transferred).

[0073] (Circuit pattern cover layer)

[0074] The circuit pattern concealing layer is a layer used to conceal the circuit pattern in the printed circuit board so that it is difficult to be recognized by the naked eye when the printed circuit board attachment film is adhered to the printed circuit board, and sometimes it also plays a role in design. of The side where the adhesive layer is located will be located on the printed circuit board of In the above-mentioned adhesive film for printed wiring boards, the above-mentioned circuit pattern covering layer can be a single layer or a plurality of layers (a laminate of a plurality of circuit pattern covering layers). When other electromagnetic wave shielding layers are included between the circuit pattern covering layer and the adhesive layer, the circuit pattern covering layer can protect the other electromagnetic wave shielding layers and the adhesive layer.

[0075] The circuit pattern covering layer may contain metal and resin as binder components. The resin may include the resins exemplified and described above as the resin contained in the resin layer. The metal may include nickel, copper, silver, tin, gold, palladium, aluminum, chromium, titanium, zinc, and alloys containing one or more of the above. The binder component may be used alone or in combination of two or more.

[0076] Among them, the binder component is preferably a resin. From the viewpoint of being able to change the close adhesion to the shape transfer film before and after curing to adjust the ease of peeling, the resin is preferably a curable resin, and from the viewpoint of being able to easily reduce the close adhesion to the shape transfer film by simultaneously curing the adhesive film for a printed wiring board when thermally pressing the adhesive film to the printed wiring board, the resin is particularly preferably a thermosetting resin.

[0077] The content ratio of the above-mentioned binder component in the above-mentioned circuit pattern covering layer is not particularly limited, and is preferably 10-70 mass %, more preferably 20-60 mass %, and further preferably 30-50 mass % relative to 100 mass % of the total amount of the above-mentioned circuit pattern covering layer.

[0078] The circuit pattern concealing layer preferably includes a black colorant from the viewpoint of being able to provide excellent hiding power. The black colorant can be a black pigment, a mixed pigment obtained by mixing a plurality of pigments to obtain a black color, etc. Examples of the black pigment include carbon black, Ketjen Black, perylene black, titanium black, iron black, and aniline black. From the viewpoint of dispersibility in the circuit pattern concealing layer, the particle size of the black pigment preferably has an average primary particle size of 20 nm or more, and more preferably 100 nm or less. The average primary particle size of the black pigment can be obtained from the average value of about 20 primary particles observed from an image magnified 50,000 to 1,000,000 times by a transmission electron microscope (TEM). The mixed pigment can be used by mixing red, green, blue, yellow, purple, cyan, magenta, and other pigments, for example. The content of the black colorant in the circuit pattern concealing layer is, for example, 0.5 to 50% by mass, preferably 1 to 40% by mass, relative to the total amount of 100% by mass of the circuit pattern concealing layer.

[0079] The circuit pattern covering layer may contain other components other than the above components within the scope that does not impair the effect of the present invention. Examples of the above other components include defoamers, viscosity modifiers, antioxidants, diluents, anti-settling agents, fillers, colorants, levelers, coupling agents, ultraviolet absorbers, tackifying resins, curing accelerators, plasticizers, flame retardants, anti-adhesion agents, curing agents, etc. The above other components may be used alone or in combination of two or more.

[0080] The 60° glossiness of the surface of the circuit pattern covering layer to which the shape transfer film is bonded is preferably 0.3 to 5.0, more preferably 0.4 to 3.0, and further preferably 0.5 to 2.0. If the 60° glossiness is 0.3 or more, it becomes easier to intentionally peel off the shape transfer film. If the 60° glossiness is 5.0 or less, the hiding power is higher. The 60° glossiness can be measured by a method according to JIS Z8741. The 60° glossiness is measured in a state where the shape transfer film is peeled off from the printed wiring board attachment film.

[0081] The 85° glossiness of the surface of the circuit pattern covering layer to which the shape transfer film is bonded is preferably 15 or less, and more preferably less than 15. If the 85° glossiness is 15 or less, the hiding power is higher. The 85° glossiness can be measured by a method in accordance with JIS Z8741. The 85° glossiness is measured in a state where the shape transfer film is peeled off from the printed wiring board attachment film.

[0082] The circuit pattern concealing layer preferably has a total light transmittance of 20% or less, more preferably 10% or less, and further preferably 5% or less. If the total light transmittance is 20% or less, it is more difficult to visually identify the circuit pattern when the printed wiring board adhesive film is bonded to the printed wiring board.

[0083] The thickness of the circuit pattern covering layer is not particularly limited and can be appropriately set as needed. From the perspectives of achieving hiding power, ease of formation, and ensuring flexibility, the thickness of the circuit pattern covering layer is preferably 1 μm or more, more preferably 4 μm or more. In addition, the thickness of the circuit pattern covering layer is preferably 20 μm or less, more preferably 10 μm or less, and further preferably 5 μm or less.

[0084] (Adhesive layer)

[0085] The adhesive layer has bonding properties for bonding the printed wiring board attachment film to the printed wiring board. The adhesive layer may be a single layer or a plurality of layers.

[0086] The adhesive layer preferably contains a binder component constituting a resin region in the adhesive layer. The binder component may include the binder components exemplified and described above as the resin contained in the resin layer. The binder component may be used alone or in combination of two or more.

[0087] When the binder component includes a thermosetting resin, the components constituting the binder component may include a curing agent for promoting a thermosetting reaction. The curing agent may be appropriately selected according to the type of the thermosetting resin. The curing agent may be used alone or in combination of two or more.

[0088] The adhesive layer may be a conductive adhesive layer. If it is a conductive adhesive layer, the adhesive layer can exhibit electromagnetic wave shielding properties. When the adhesive layer is a conductive adhesive layer, it is preferred that it further contains conductive particles.

[0089] Examples of the conductive particles include metal particles, metal-coated resin particles, metal fibers, carbon-based fillers, etc. The conductive particles may be used alone or in combination of two or more.

[0090] Examples of the metal particles, the metal constituting the coating of the metal-coated resin particles, and the metal constituting the metal fibers include gold, silver, copper, nickel, zinc, etc. The metals may be used alone or in combination of two or more.

[0091] Specifically, the metal particles include, for example, copper particles, silver particles, nickel particles, silver-coated copper particles, gold-coated copper particles, silver-coated nickel particles, gold-coated nickel particles, silver-coated alloy particles, etc. The silver-coated alloy particles include, for example, silver-coated copper alloy particles obtained by coating copper-containing alloy particles (e.g., copper alloy particles composed of an alloy of copper, nickel, and zinc) with silver, etc. The metal particles can be produced by electrolysis, atomization, reduction, etc.

[0092] Among them, the metal particles are preferably silver particles, silver-coated copper particles, and silver-coated copper alloy particles. Silver-coated copper particles and silver-coated copper alloy particles are particularly preferred from the viewpoints of excellent conductivity, ability to suppress oxidation and coagulation of the metal particles, and reduced cost of the metal particles.

[0093] Examples of the shape of the conductive particles include spherical, flake (scale), dendritic, fibrous, and amorphous (polyhedral).

[0094] The median diameter (D50) of the conductive particles is preferably 1 to 50 μm, more preferably 3 to 40 μm. When the median diameter is 1 μm or more, the conductive particles have good dispersibility, can suppress coagulation, and are difficult to oxidize. When the average particle diameter is 50 μm or less, the conductivity is good. The D50 refers to the particle diameter at the cumulative value of 50% in the particle size distribution obtained by the laser diffraction / scattering method.

[0095] The conductive adhesive layer may have isotropic conductivity or anisotropic conductivity as required.

[0096] If the adhesive layer is a conductive adhesive layer, the content of the binder component in the adhesive layer is not particularly limited, and is preferably 5 to 60% by mass, more preferably 10 to 50% by mass, and further preferably 20 to 40% by mass relative to the total amount 100% by mass of the adhesive layer. If the content is 5% by mass or more, the electromagnetic shielding performance is good. If the content is 60% by mass or less, the close adhesion to the printed wiring board is more excellent.

[0097] If the adhesive layer is a conductive adhesive layer, the content of the conductive particles in the adhesive layer is not particularly limited, and is preferably 2 to 95% by mass, more preferably 5 to 80% by mass, and further preferably 10 to 70% by mass relative to the total amount 100% by mass of the adhesive layer. If the content is 2% by mass or more, the conductivity is better. If the content is 95% by mass or less, the adhesive component can be fully contained, and the close adhesion to the printed wiring board is better.

[0098] The adhesive layer may contain other ingredients other than the above-mentioned ingredients within the scope of not damaging the effect of the present invention. The above-mentioned other ingredients can list well-known and even commonly used ingredients contained in the adhesive layer. The above-mentioned other ingredients can, for example, list defoamers, viscosity modifiers, antioxidants, diluents, anti-settling agents, fillers, colorants, levelers, coupling agents, ultraviolet light absorbers, tackifying resins, curing accelerators, plasticizers, flame retardants, anti-blocking agents, etc. The above-mentioned other ingredients can be used only one, or two or more.

[0099] The thickness of the adhesive layer is preferably 3 to 20 μm, more preferably 5 to 15 μm. When the thickness is 3 μm or more, the adhesion to the printed wiring board is further improved.

[0100] The above-mentioned adhesive film for printed circuit boards may contain the above-mentioned shape transfer film, the above-mentioned circuit pattern covering layer, and other layers other than the above-mentioned adhesive layer. The above-mentioned other layers can include other electromagnetic wave shielding layers other than the above-mentioned conductive adhesive layer, such as a metal layer provided between the above-mentioned circuit pattern covering layer and the above-mentioned adhesive layer. In addition, when the above-mentioned other electromagnetic wave shielding layer is included, the above-mentioned other layers can include an adhesion-promoting coating provided between the above-mentioned circuit pattern covering layer and the above-mentioned other electromagnetic wave shielding layer.

[0101] Examples of the metal constituting the metal layer include gold, silver, copper, aluminum, nickel, tin, palladium, chromium, titanium, zinc, or alloys of the metals. The metal layer is preferably a metal plate or a metal foil. That is, the metal layer is preferably a copper plate (copper foil) or a silver plate (silver foil).

[0102] The materials for forming the above-mentioned adhesion-promoting coating layer include polyurethane resin, acrylic resin, core-shell composite resin with polyurethane resin as shell and acrylic resin as core, epoxy resin, polyimide resin, polyamide resin, melamine resin, phenol resin, urea-formaldehyde resin, blocked isocyanate obtained by reacting blocking agents such as phenol with polyisocyanate, polyvinyl alcohol, polyvinyl pyrrolidone, etc. The above-mentioned materials may be used alone or in combination of two or more.

[0103] The peeling force (first peeling force) of the shape transfer film relative to the circuit pattern masking layer in the above-mentioned adhesive film for printed wiring boards is preferably 0.1N or more, more preferably 0.2N or more, and further preferably 0.3N or more. If the first peeling force is 0.1N or more, it is difficult to peel off during transportation, etc., and unintentional peeling can be suppressed. The first peeling force can be measured by the method described in the examples.

[0104] The peeling force (second peeling force) of the shape transfer film relative to the circuit pattern masking layer after the adhesive layer of the above-mentioned printed wiring board attachment film is adhered to the printed wiring board and attached by heating and pressing is preferably 3.0N or less, more preferably 2.0N or less, and further preferably 1.5 or less. If the second peeling force is 3.0N or less, the shape transfer film can be easily peeled off when it is intentionally peeled off during use. The second peeling force can be measured by the method described in the examples.

[0105] The ratio of the second peeling force to the first peeling force [second peeling force / first peeling force] is preferably 0.5 to 1.5, more preferably 0.6 to 1.3, and further preferably 0.7 to 1.2. If the ratio is within the above range, unintentional peeling can be further suppressed, and peeling can be performed more easily when intentional peeling is performed during use.

[0106] The above-mentioned adhesive film for a printed wiring board is particularly preferably used for a flexible printed wiring board (FPC). The above-mentioned adhesive film for a printed wiring board can be preferably used as an adhesive film for a flexible printed wiring board.

[0107] (Method for manufacturing adhesive film for printed wiring board)

[0108] The method for producing the above-mentioned adhesive film for printed wiring board is described. Figure 3 In the production process of the printed wiring board attachment film 5 shown, the adhesive layer 7 and the circuit pattern concealing layer 6 are first produced separately. Thereafter, the adhesive layer 7 and the circuit pattern concealing layer 6 produced separately are bonded together (lamination method).

[0109] The adhesive layer 7 can be formed, for example, by applying (coating) the adhesive composition for forming the adhesive layer 7 onto a temporary substrate such as a release film or onto a substrate, and removing the solvent and / or partially curing the adhesive composition as necessary.

[0110] The adhesive composition, for example, includes a solvent (solvent) in addition to the components contained in the adhesive layer. Examples of the solvent include toluene, acetone, methyl ethyl ketone, methanol, ethanol, propanol, dimethylformamide, etc. The solid content concentration of the adhesive composition is appropriately set according to the thickness of the adhesive layer to be formed.

[0111] The adhesive composition can be applied by a well-known coating method, for example, a coating machine such as a gravure roll coater, a reverse roll coater, an oiling roll coater, a lip coater, a dip roll coater, a bar coater, a knife coater, a spray coater, a comma coater, a direct coater, or a slit coater can be used.

[0112] On the other hand, the circuit pattern covering layer 6 can be formed as follows: when a resin is used as a binder component, for example, a resin composition for forming the circuit pattern covering layer 6 is applied (coated) to the surface of the shape transfer film on which the above-mentioned concavo-convex shape is formed, and the solvent is removed and / or partially cured as needed to cure. In this way, the surface of the circuit pattern covering layer 6 can be given a shape derived from the concavo-convex shape surface of the shape transfer film 1.

[0113] The resin composition, for example, further comprises a solvent (solvent) in addition to the components contained in the circuit pattern covering layer. The solvent can include the solvents exemplified above as the adhesive composition containing solvents. The solid content concentration of the resin composition is appropriately set according to the thickness of the circuit pattern covering layer to be formed.

[0114] The resin composition can be applied by a known coating method, for example, the coating machine exemplified above as used for the adhesive composition application.

[0115] Next, the exposed surface of the adhesive layer 7 and the exposed surface of the circuit pattern concealing layer 6 which have been separately prepared are bonded together to prepare the adhesive film 5 for the printed wiring board.

[0116] As another form other than the above-mentioned lamination method, the above-mentioned printed wiring board adhesive film can also be manufactured by a method of sequentially laminating each layer (direct coating method). For example, Figure 3The attached film 5 for printed wiring board shown can be manufactured as follows: a resin composition for forming a circuit pattern covering layer 6 is coated (applied) on the surface of the adhesive layer 7, and the circuit pattern covering layer 6 is formed by removing the solvent and / or partially curing it as needed. In this case, the concave-convex shape surface of the shape transfer film 1 is stacked on the layer of the above-mentioned resin composition before complete curing, and then it is completely cured, thereby giving the surface of the formed circuit pattern covering layer 6 a shape derived from the above-mentioned concave-convex shape. Alternatively, it can be manufactured as follows: first, a circuit pattern covering layer 6 is formed on the concave-convex shape surface of the shape transfer film 1, and an adhesive composition for forming an adhesive layer 7 is coated (applied) on the surface of the circuit pattern covering layer 6, and the adhesive layer 7 is formed by removing the solvent and / or partially curing it as needed. Example

[0117] The present invention will be described in further detail below based on examples, but the present invention is not limited to these examples.

[0118] Example 1

[0119] (Production of shape transfer film)

[0120] A resin composition consisting of 30 parts by mass of silica particles (D50: 6.5 μm), 100 parts by mass of melamine resin, and toluene was prepared, and the resin composition was applied to the surface of a 25 μm thick polyethylene terephthalate film using a wire bar. The solvent was removed by heating to produce a shape transfer film having a 5 μm thick resin layer on the surface of a substrate layer.

[0121] (Production of adhesive film)

[0122] A resin composition was prepared by mixing 100 parts by mass of a bisphenol A epoxy resin (trade name "jER1256", manufactured by Mitsubishi Chemical Corporation), 0.1 parts by mass of a curing agent (trade name "ST14", manufactured by Mitsubishi Chemical Corporation), and 15 parts by mass of carbon particles (trade name "TOKABLACK #8300 / F", manufactured by Tokai Carbon Co., Ltd.) as a black colorant into toluene so that the solid content was 20% by mass. The resin composition was applied to the surface of the resin layer of the shape transfer film using a wire bar, and cured by heating to form a circuit pattern masking layer with a thickness of 5 μm on the surface of the shape transfer film.

[0123] Next, 100 parts by mass of bisphenol A epoxy resin (trade name "jER1256", manufactured by Mitsubishi Chemical Corporation) and 0.1 parts by mass of curing agent (trade name "ST14", manufactured by Mitsubishi Chemical Corporation) were mixed into toluene to obtain a solid content of 20% by mass, and the mixture was stirred and mixed to prepare an adhesive layer composition. The adhesive layer composition was applied to a PET film (hereinafter referred to as a support film) with a release treatment on the surface using a wire bar, and cured by heating to form an adhesive layer with a thickness of 5 μm on the surface of the support film.

[0124] Next, the circuit pattern masking layer formed on the surface of the shape transfer film and the adhesive layer formed on the surface of the support film were bonded, and heated and pressed at a pressure of 5 MPa using a pair of metal rollers heated to 100° C. to obtain an attached film. The total light transmittance of the obtained attached film was 5% or less.

[0125] (Preparation of evaluation substrate)

[0126] The attached film obtained by the above process was stacked on the printed circuit board, and then a press was used to evacuate for 60 seconds under the conditions of temperature: 170°C and pressure: 2MPa, and then heated and pressed for 180 seconds to bond, and an evaluation substrate was prepared. The above-mentioned printed circuit board used a printed circuit board with a circuit pattern formed on a base layer composed of a polyimide film. The above-mentioned circuit pattern is formed by a copper foil with a line width of 0.1mm and a height of 12μm. On the above-mentioned base layer, a 25μm thick adhesive layer and a 12.5μm thick cover film (insulating film) composed of a polyimide film are provided to cover the circuit pattern.

[0127] Example 2

[0128] A shape transfer film, an attachment film, and a base material for evaluation were prepared in the same manner as in Example 1 except that a resin layer having a thickness of 7 μm was formed on the surface of the substrate layer.

[0129] Example 3

[0130] A shape transfer film, an attachment film, and a substrate for evaluation were prepared in the same manner as in Example 1 except that silica particles having a D50 of 4.5 μm were used.

[0131] Example 4

[0132] A shape transfer film, an attachment film, and a substrate for evaluation were prepared in the same manner as in Example 1 except that silica particles having a D50 of 3.8 μm were used.

[0133] Comparative Example 1

[0134] A shape transfer film, an attachment film, and a substrate for evaluation were prepared in the same manner as in Example 1 except that silica particles having a D50 of 9 μm were used.

[0135] Comparative Example 2

[0136] A shape transfer film, an attachment film, and a substrate for evaluation were prepared in the same manner as in Example 1 except that silica particles having a D50 of 10 μm were used.

[0137] Comparative Example 3

[0138] A shape transfer film, an attachment film, and a base material for evaluation were prepared in the same manner as in Example 1 except that silica particles having a D50 of 3.5 μm were used and a resin layer having a thickness of 3 μm was formed on the surface of the substrate layer.

[0139] Comparative Example 4

[0140] A shape transfer film, an attachment film, and a base material for evaluation were prepared in the same manner as in Comparative Example 3 except that a 4 μm-thick resin layer was formed on the surface of the substrate layer.

[0141] Comparative Example 5

[0142] As the shape transfer film, a film having a concavo-convex shape having the performance shown in Table 1 was used. Then, a sticking film and a substrate for evaluation were prepared in the same manner as in Example 1 except that the shape transfer film was used.

[0143] Comparative Example 6

[0144] As the shape transfer film, a film having a concavo-convex shape having the properties shown in Table 1 obtained by kneading a filler into a polyethylene terephthalate resin and molding was used. Then, a pasting film and an evaluation substrate were prepared in the same manner as in Example 1 except that the shape transfer film was used.

[0145] Comparative Example 7

[0146] As the shape transfer film, a film having a concavo-convex shape having properties shown in Table 1 obtained by kneading a filler into a polyethylene terephthalate resin and molding was used. Then, a pasting film and an evaluation substrate were prepared in the same manner as in Example 1 except that the shape transfer film was used.

[0147] Comparative Example 8

[0148] As the shape transfer film, a film having a concavo-convex shape having properties shown in Table 1 obtained by sandblasting the surface of a polyethylene terephthalate film was used. Then, a pasting film and an evaluation substrate were prepared in the same manner as in Example 1 except that the shape transfer film was used.

[0149] (evaluate)

[0150] The shape transfer films, attachment films, and evaluation substrates obtained in Examples and Comparative Examples were evaluated as follows. The evaluation results are shown in the table.

[0151] (1) Surface shape

[0152] Using a confocal microscope (trade name "OPTELICS HYBRID", manufactured by Lasertec, objective lens 100 times), the interface development area ratio Sdr, the level difference Sk at the center, the arithmetic mean height Sa, the root mean square height Sq, and the arithmetic mean of the root mean square slope Sdq were measured for the concave-convex shapes formed at any five locations on the surface of the resin layer of the shape transfer film in accordance with ISO 25178. The cutoff wavelength of the S filter was 0.0025 mm, and the cutoff wavelength of the L filter was 0.8 mm.

[0153] (2) Glossiness

[0154] The 60° gloss and 85° gloss of the concavo-convex shape formed on the resin layer surface of the shape transfer film and the 60° gloss and 85° gloss of the region on the surface of the circuit pattern cover layer in the evaluation substrate to which the concavo-convex shape was transferred were measured using a Gardner micro-gloss meter (portable gloss meter, manufactured by BYK). In addition, the gloss of the circuit pattern cover layer surface was measured on the surface after the shape transfer film was peeled off from the evaluation substrate.

[0155] (3) Peel force before heating and pressurization (1st peel force)

[0156] The peeling force when the shape transfer film is peeled off from the attached film (before heating and pressing) prepared in the above-mentioned examples and comparative examples was measured as the first peeling force. Specifically, the attached film was fixed to a polyimide film having a thickness of 100 μm, and the peeling force (first peeling force) when the shape transfer film was peeled off from the attached film was evaluated using a strength tester (trade name "PFT50S", manufactured by Pallmec Co., Ltd.) under the conditions of a sample width of 10 mm, a peeling angle of 170°, and a peeling speed of 1000 mm / min.

[0157] (4) Peel force after heating and pressurization (second peel force)

[0158] When preparing the above-mentioned evaluation substrate, the peeling force when peeling the shape transfer film from the state after heating and pressing was measured as the second peeling force. Specifically, the peeling force (second peeling force) when peeling the shape transfer film from the evaluation substrate was evaluated using a strength tester (trade name "PFT50S", manufactured by Pallmec Co., Ltd.) under the conditions of a sample width of 10 mm, a peeling angle of 170°, and a peeling speed of 1000 mm / min.

[0159] (5) Covering

[0160] The evaluation substrate was placed on a flat table, and after peeling off the shape transfer film, the circuit pattern was evaluated to see whether the circuit pattern could be visually recognized from the circuit pattern masking layer side at a height of 30 cm and an angle of 45° under an environment where the illumination of the circuit board surface was shielded at 500 lux. If the circuit pattern could not be visually recognized, the hiding power was evaluated as good (○), and if the circuit pattern could be visually recognized, the hiding power was evaluated as poor (×).

[0161] [Table 1]

[0162]

[0163] Regarding the shape transfer film of the embodiment, the circuit pattern covering layer formed using the shape transfer film has excellent covering property, and the peeling force (second peeling force) after heating and pressing is as low as 2.0N or less, and the peeling property from the circuit pattern covering layer is also excellent. In addition, the peeling force (first peeling force) before heating and pressing is 0.1N or more, indicating that the shape transfer film is difficult to peel off unintentionally. On the other hand, when the interface development area of ​​the shape transfer film surface is larger than Sdr or the level difference Sk of the center (Comparative Examples 1 and 2), the second peeling force exceeds 2.0N, and the peeling property from the circuit pattern covering layer is poor. In addition, when the interface development area of ​​the shape transfer film surface is smaller than Sdr or the level difference Sk of the center (Comparative Examples 3 to 8), the covering property of the circuit pattern covering layer is poor. In addition, in Comparative Example 8, the second peeling force exceeds 2.0N, and the peeling property from the circuit pattern covering layer is also poor.

[0164] Number Description

[0165] 1 Shape transfer film

[0166] 2. Substrate layer

[0167] 3 Resin layer

[0168] 4. Filling

[0169] 5 Attachment film for printed circuit boards

[0170] 6 Circuit pattern cover layer

[0171] 7 Adhesive layer

[0172] 2a, 3a Shape transfer film flat surface

Claims

1. A shape transfer film, characterized in that: The shape transfer film has a concavo-convex shape having an interface development area ratio Sdr of 1500 to 7000% on at least one side thereof, and is used to transfer a shape derived from the concavo-convex shape to a transfer object, wherein the interface development area ratio Sdr is measured in accordance with ISO25178; The shape transfer film is the following i) or ii): i) a shape transfer film including a substrate layer and a resin layer provided on at least one side of the substrate layer, wherein the surface of the shape transfer film on the side of the resin layer contains the concavo-convex shape, and the resin forming the resin layer is at least one selected from a thermosetting resin and an active energy ray-curable resin, ii) comprising a substrate layer, wherein the substrate layer has a shape transfer film having the concavo-convex shape on its surface; Furthermore, the shape transfer film is attached to the transfer object to form an attached film, and the peeling force before heating and pressurizing is greater than 0.1N. The peeling force is measured by the following method: using a strength tester PFT50S, under the conditions of the attached film width of 10mm, the peeling angle of 170°, and the peeling speed of 1000mm / min, the peeling force when the shape transfer film is peeled off from the attached film is measured.

2. The shape transfer film according to claim 1, characterized in that: The interface development area ratio Sdr in the concavo-convex shape is 2500 to 6000%.

3. The shape transfer film according to claim 1, characterized in that: The level difference Sk of the center portion of the concavo-convex shape is 2.0 to 7.0 μm, The level difference Sk of the center portion is measured in accordance with ISO25178.

4. A shape transfer film, characterized in that: The shape transfer film has a concavo-convex shape with a center level difference Sk of 2.0 to 7.0 μm on at least one side thereof, and is used to transfer a shape derived from the concavo-convex shape to a transfer object, wherein the center level difference Sk is measured in accordance with ISO 25178; The shape transfer film is the following i) or ii): i) a shape transfer film including a substrate layer and a resin layer provided on at least one side of the substrate layer, wherein the surface of the shape transfer film on the side of the resin layer contains the concavo-convex shape, and the resin forming the resin layer is at least one selected from a thermosetting resin and an active energy ray-curable resin, ii) comprising a substrate layer, wherein the substrate layer has a shape transfer film having the concavo-convex shape on its surface; Furthermore, the shape transfer film is attached to the transfer object to form an attached film, and the peeling force before heating and pressurizing is greater than 0.1N. The peeling force is measured by the following method: using a strength tester PFT50S, under the conditions of the attached film width of 10mm, the peeling angle of 170°, and the peeling speed of 1000mm / min, the peeling force when the shape transfer film is peeled off from the attached film is measured.

5. The shape transfer film according to claim 4, characterized in that: The level difference Sk of the center portion of the concavo-convex shape is 2.5 to 5.0 μm.

6. The shape transfer film according to claim 1 or 4, characterized in that: The arithmetic mean height Sa of the concavo-convex shape is 1.0 to 2.0 μm, The arithmetic mean height Sa is measured in accordance with ISO25178.

7. The shape transfer film according to claim 1 or 4, characterized in that: The root mean square height Sq of the concavoconvex shape is 1.0 to 2.8 μm, The root mean square height Sq is measured according to ISO25178.

8. The shape transfer film according to claim 1 or 4, characterized in that: The root mean square slope Sdq of the concavo-convex shape is 7 to 15, The root mean square slope Sdq is measured according to ISO25178.

9. The shape transfer film according to claim 1 or 4, characterized in that: In the concavo-convex shape, a ratio [Sdr / Sdq] of an interface developed area ratio Sdr to a root mean square slope Sdq is 200 to 500.

10. The shape transfer film according to claim 1 or 4, characterized in that: The shape transfer film contains a filler, and the concavo-convex shape is formed by the filler protruding outward from a flat surface of the film.

11. An attachment film for a printed circuit board, characterized in that: The attachment film for a printed wiring board comprises the shape transfer film according to any one of claims 1 to 10 and a circuit pattern covering layer directly laminated on the shape transfer film.

12. The adhesive film for a printed circuit board according to claim 11, characterized in that: The adhesive layer, the circuit pattern covering layer, and the shape transfer film are stacked in sequence.

13. The adhesive film for a printed circuit board according to claim 12, characterized in that: The 85° glossiness of the shape transfer film side surface of the circuit pattern covering layer is less than 15, The 85° glossiness is measured in accordance with JIS Z8741.

Citation Information

Patent Citations

  • Biaxially oriented polyester film having matte layer

    JP2017071107A

  • Biaxially oriented polyester film

    CN107073916A